Using Optimization Techniques on Mechanical Characteristics and Sustainability Assessment of Rubberized Concrete Blended with PVA Fiber Through Response Surface Methodology - Naraindas Bheel; Abhijeet Vidyadhar Baikerikar; Bashar S. Mohammed (International Journal of Concrete Structures and Materials)
Abstract The construction sector is promoting eco-friendly materials to combat global warming. Researchers use crumb rubber (CR) in concrete due to its ductility and hardness, but studies show it can decrease strength. Therefore, the addition of PVA fiber improves the mechanical properties of CR concrete. The research aims to assess the mechanical and physical characteristics of concrete by utilizing RSM modeling and optimization, comparing the effects of CR replacement for sand and PVA fiber by volume fraction. It has been observed that the optimum compressive, tensile and flexural strengths were observed by 49 MPa, 4.31 MPa, and 5.88 MPa at 10% of sand replaced with CR and 1.5% of PVA fiber together at 28 days, respectively. In addition, water absorption improves with increased CR and PVA fiber in concrete, while dry density decreases with increased CR and PVA fiber quantity in concrete at 28 days, respectively. Moreover, RSM was utilized to develop response prediction models with R2 coefficients ranged from 97 to 99%. Furthermore, the enhancement of embodied carbon is seen when the volume percent of PVA fiber and CR increases in concrete. Additionally, using 10% CR instead of sand and adding 1.5% PVA fiber has been proven to deliver favourable outcomes for the construction sector therefore it is recommended for construction purpose.